Analisis Penerapan Nilai Pancasila sebagai Dasar Pengembangan Pendidikan Inklusif di Universitas Pendidikan Indonesia: Studi Kualitatif - Azkiya, Nasywa Nurul; Ghassan, Muhammad Ghiyats Zainul; Asy Syifa, Salma Nur; Fitria, Khodijah; Prandyatama, Ritonga Muhammad Farrel Halomoan; Supriyono, Supriyono (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
Inclusive education is an educational system that ensures everyone receives equal and fair access to learning, including students with disabilities. However, its implementation in Indonesian higher education institutions still faces various challenges, such as structural, cultural, and methodological barriers. The values of Pancasila particularly humanity, unity, and social justice are relevant as moral and ethical foundations. This study evaluates the implementation of inclusive education at Universitas Pendidikan Indonesia (UPI) by emphasizing the role of Pancasila values in creating an inclusive academic environment. Using a descriptive qualitative approach, the study involved participants consisting of one lecturer, one student with disabilities (categorized as having physical and sensory disabilities), and two non-disabled students. Data were collected through in-depth interviews, classroom observations, and documentation studies, and were analyzed using thematic analysis. Data validity was ensured through source triangulation and member checking. The results indicate that the academic community perceives Pancasila as the moral foundation of inclusive education and provides instrumental, emotional, and academic support through mentoring, flexibility in assignments, and service policies. However, the implementation has not been evenly distributed across all faculties, due to limited accessibility facilities, learning media that are not disability-friendly, a lack of sign language interpreters, and insufficient training for lecturers. A gap is evident between normative understanding and the practical realization of social justice in fulfilling the academic rights of students with disabilities.This study concludes that the implementation of inclusive education at UPI operates at a normative level but has not yet reached optimal practice. Therefore, strengthening institutional policies, enhancing lecturers’ competencies, providing physical and digital accessibility facilities, and continuously internalizing Pancasila values are necessary to realize higher education that is just, humane, and sustainable. The main contribution of this study is to offer practical recommendations for Indonesian higher education institutions to improve the implementation of inclusive education by reinforcing Pancasila values as an ethical and moral foundation.ABSTRAKPendidikan inklusif adalah sistem pendidikan yang memastikan setiap orang mendapatkan hak belajar secara adil, termasuk mahasiswa disabilitas, namun, penerapannya di perguruan tinggi Indonesia masih menghadapi tantangan, seperti struktural, budaya, dan metodologis. Nilai-nilai Pancasila, khususnya kemanusiaan, persatuan, dan keadilan sosial, relevan sebagai dasar moral dan etika. Penelitian ini mengevaluasi implementasi pendidikan inklusif di Universitas Pendidikan Indonesia (UPI) dengan menekankan peran nilai-nilai Pancasila dalam menciptakan lingkungan akademik yang inklusif. Menggunakan metode kualitatif deskriptif, penelitian melibatkan subjek terdiri dari 1 dosen, 1 mahasiswa disabilitas (berkategori fisik, sensorik), dan 2 mahasiswa non-disabilitas. Data dikumpulkan melalui wawancara mendalam, observasi perkuliahan, dan studi dokumentasi, kemudian dianalisis menggunakan analisis tematik serta diuji keabsahannya melalui triangulasi sumber dan member checking. Hasil menunjukkan civitas akademika memaknai Pancasila sebagai fondasi moral pendidikan inklusif, memberikan dukungan instrumental, emosional, dan akademik melalui pendampingan, fleksibilitas penugasan, serta kebijakan layanan. Namun, implementasi belum merata ke seluruh fakultas, dengan keterbatasan fasilitas aksesibilitas, media pembelajaran yang kurang ramah disabilitas, minimnya juru bahasa isyarat, dan kurangnya pelatihan bagi dosen. Terlihat adanya Kesenjangan antara pemahaman normatif dan praktik keadilan sosial dalam memenuhi hak hak akademik mahasiswa disabilitas. Penelitian ini menyimpulkan implementasi pendidikan inklusif di UPI berjalan normatif namun belum optimal, sehingga diperlukan penguatan kebijakan institusional, peningkatan kompetensi dosen, penyediaan fasilitas aksesibilitas fisik dan digital, serta internalisasi nilai-nilai Pancasila yang berkelanjutan untuk mewujudkan pendidikan tinggi yang adil, humanis, dan berkelanjutan. Kontribusi utama penelitian ini adalah memberikan rekomendasi praktis bagi perguruan tinggi Indonesia untuk meningkatkan implementasi pendidikan inklusif melalui penguatan nilai-nilai Pancasila sebagai landasan yang etis dan moral.